2022
DOI: 10.1186/s13006-022-00462-z
|View full text |Cite
|
Sign up to set email alerts
|

Enablers and inhibitors of exclusive breastfeeding: perspectives from mothers and health workers in Accra, Ghana

Abstract: Background Despite the health and economic benefits of exclusive breastfeeding, there is evidence of a decline globally and in Ghana. Previous studies addressing this problem are mostly quantitative with only a few of such studies using qualitative or mixed methods to examine the predictors, benefits, ways of improving and managing exclusive breastfeeding, and the challenges associated with exclusive breastfeeding from the perspective of exclusive and nonexclusive breastfeeding mothers, and hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…The study utilized the SEM approach and interviewed breastfeeding mothers to understand, mostly, their microsystem of breastfeeding facilitators and barriers ( 60 , 61 ). This study further identified factors that should be considered to improve continuous breastfeeding, including exclusive breastfeeding, like other research areas of improvement ( 13 , 41 ). Mothers lived in poor socioeconomic households and most were unmarried, unemployed, received minimal income, and had low tertiary education, while poor obstetric history was characterized by unplanned pregnancy, late or zero attendance at antenatal care, cesarean mode of delivery, and mothers living with HIV, similar to other studies ( 62 , 63 ).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The study utilized the SEM approach and interviewed breastfeeding mothers to understand, mostly, their microsystem of breastfeeding facilitators and barriers ( 60 , 61 ). This study further identified factors that should be considered to improve continuous breastfeeding, including exclusive breastfeeding, like other research areas of improvement ( 13 , 41 ). Mothers lived in poor socioeconomic households and most were unmarried, unemployed, received minimal income, and had low tertiary education, while poor obstetric history was characterized by unplanned pregnancy, late or zero attendance at antenatal care, cesarean mode of delivery, and mothers living with HIV, similar to other studies ( 62 , 63 ).…”
Section: Discussionmentioning
confidence: 86%
“…In addition, mothers believed that eating healthy foods, such as salted ground nuts, soft porridge, water and tea, and maize-based foods, enabled breastfeeding by producing sufficient breast milk, supported by other research showing that adequate maternal nutrition plays a role in facilitating breastfeeding ( 70 , 73 , 74 ). It is, therefore, important to have nutritionists based at health facilities, especially in rural areas, to provide advice to mothers on the specific type of food to eat in order to produce breast milk ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Socioeconomic indicators such as income level, maternal health condition or mental state relation, parity, maternal age, gestational age, educational level, occupation and employment issues were perceived as major confounders to the multiple logistic regression model. These were chosen because many previous studies [14,[17][18][19][20] have reported the influence of socio-economic and cultural factors on the practice of EBF. Missing data was managed using a listwise or case deletion.…”
Section: Discussionmentioning
confidence: 99%
“…In order to maximize positive perception and attitude toward the practice of EBF in these areas, educational interventions to help women better understand the benefits of EBF is required. While studies on exclusive breastfeeding in Ghana have focused on the knowledge level, socioeconomic and cultural practices as being the major factors affecting the practice of EBF [13,[16][17][18][19], information on the effect of family support from parents, spouse and healthcare professionals on the practice of EBF has remained inadequate.…”
Section: Introductionmentioning
confidence: 99%